Technical Writing for Success, 4th Edition - Darlene Smith-Worthington; Sue Jefferson (Cengage Learning, 2018)
TECHNICAL WRITING FOR SUCCESS, Fourth Edition, gives you writing skills to match your ambition. Whether your passion is writing for business, high-tech, science, or the Web, you'll develop abilities that can make your technical writing shine. Created by writing pros who know what employers demand, this text trains you on the essentials of clear technical communications: thinking, listening, composing, revising, and editing. Instead of reading and hoping, you'll learn by doing, practicing with the many Microsoft Office documents provided in the text for reference. To prepare you for a job in a real office with real people, you get helpful strategies for improving workplace communications, including word choice, tone, and clarity, and even how to turn bad news into a positive result. Let TECHNICAL WRITING FOR SUCCESS help you master the craft of technical writing!